2018
DOI: 10.1021/acs.joc.8b02282
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/Norbornene Chemistry: Synthesis of Norbornene-Containing Arylsilanes Involving Double C–Si Bond Formation

Abstract: A novel palladium-catalyzed three-component cascade reaction of aryl halides with norbornene and hexamethyldisilane has been described, which allows the simultaneous construction of two C–Si bonds and one C–C bond. The method achieves ortho C–H functionalization of aryl halides through the formation of the five-membered palladacycle, leading to norbornene-containing arylsilanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 74 publications
2
8
0
Order By: Relevance
“…Later, it was shown that the use of anilines or ureas could lead to similar products . Recently, disilanes was also found to be able to intercept the ANP intermediate by the Zhang, Cheng, , and Liang groups. Due to the facile C–Si reductive elimination, NBE-containing bis-silylated products were obtained.…”
Section: Catalytic Reactionsmentioning
confidence: 99%
“…Later, it was shown that the use of anilines or ureas could lead to similar products . Recently, disilanes was also found to be able to intercept the ANP intermediate by the Zhang, Cheng, , and Liang groups. Due to the facile C–Si reductive elimination, NBE-containing bis-silylated products were obtained.…”
Section: Catalytic Reactionsmentioning
confidence: 99%
“…Very recently, the Chen , and Our groups simultaneously demonstrated palladium-catalyzed Catellani-type ortho -silylation of aryl iodides. On the basis of recent reports and our ongoing interests in the tandem reactions involving palladacycles, herein we successfully achieved palladium-catalyzed interannular meta -C–H silylation/ ortho -C–H alkylation for building silicon-containing 1,1′-biaryl-2-acetamides from 1,1′-biaryl-2-acetamides with hexamethyldisilane in the presence of NBE (Scheme -3). Interestingly, the strategy could be expanded to interannular meta -C–H silylation/ ortho -C–H alkenylation of 1,1′-biaryl-2-acetamides by the use of ONBD, instead of NBE and interannular ortho -C–H silylation of 1,1′-biaryl-2-acetamides, in the absence of NBE.…”
mentioning
confidence: 99%
“…13 C{ 1 H} NMR (100 MHz, CDCl 3 ) δ 154.2, 133.2, 129.7, 128.6, 47.4, 44.2, 41.7, 38.8, 37.8, 32.9, 0.7, −0.9. The spectral data were in accordance with the literature …”
Section: Methodsmentioning
confidence: 99%
“…The spectral data were in accordance with the literature. 19 Trimethyl((2R,3R)-3- (3-(trimethylsilyl)-[1,1′-biphenyl]-4-yl)bicyclo[2.2.1]heptan-2-yl)silane (2b). Purification by column chromatography on silica gel (eluent: petroleum ether) afforded 2b as a colorless oil liquid, isolated yield 61% (120 mg).…”
Section: Trimethyl(2-((2r3r)-3-(trimethylsilyl)bicyclo[221]heptan-2-y...mentioning
confidence: 99%
See 1 more Smart Citation